1974
DOI: 10.1111/j.1432-1033.1974.tb03747.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ganglioside GGtet1 and Its Derivatives with Choleragen

Abstract: It was confirmed that ganglioside GGtetl, i.e. GalPl + 3GalNAcPl + 4[NeuNAca2 + 3lGalB1 + 4Glc-ceramide, specifically interacts with choleragen (cholera-exoenterotoxin) as shown by precipitate formation and inhibition of the toxicity. The isolated carbohydrate moiety of ganglioside GGtetl, i.e. GGtetl minus ceramide, neither precipitated choleragen nor interferred with the reaction between the toxin and its antibody. However, polyacrylamide gel electrophoresis revealed a specific interaction between the sialo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…The DANSyl gangliosidoi'de or ganglioside GGt,tl, both at concentrations of 0.1 pmol/ml of the above-mentioned buffer were mixed with aliquots of the solution of protein I. Mixtures at molar ratios of 0.1: 1, 1: 1, 2: 1, and 4: 1 for the glycolipid and protein I complexes were prepared. Precipitate formation was visually estimated 20 h later and the inhibition of immunoprecipitates was evaluated by immunodiffusion against antiserum to protein I, essentially as described earlier [9] .…”
Section: Precipitation Of Cholera Toxin-subunit-protein I With Dansylmentioning
confidence: 99%
See 1 more Smart Citation
“…The DANSyl gangliosidoi'de or ganglioside GGt,tl, both at concentrations of 0.1 pmol/ml of the above-mentioned buffer were mixed with aliquots of the solution of protein I. Mixtures at molar ratios of 0.1: 1, 1: 1, 2: 1, and 4: 1 for the glycolipid and protein I complexes were prepared. Precipitate formation was visually estimated 20 h later and the inhibition of immunoprecipitates was evaluated by immunodiffusion against antiserum to protein I, essentially as described earlier [9] .…”
Section: Precipitation Of Cholera Toxin-subunit-protein I With Dansylmentioning
confidence: 99%
“…The glycolipid ganglioside GG,J* which occurs localised in the plasma membrane of mammalian cells is known to interact strongly and specifically with cholera toxin [8,9]. Using fluoresceine-labelled cholera toxin, Craig and Cuatrecasas [lo] have demonstrated a redistribution and cap formation on the surface of lymphocytes which was temperaturedependent and sensitive for metabolic inhibitors.…”
mentioning
confidence: 99%
“…Experiments with purified NANase and 125I-labeled CTX showed that isolated rabbit small-intestine brush borders or cultured mouse neuroblastoma cells exposed to NANase bound 2 to 7 times more CTX than did untreated cells (Griffiths et al, 1986;Miller-Podraza et al, 1982). In ligated canine ileal loops injected with CTX, secretion increased fourfold in loops pretreated with NANase compared with untreated control loops (Staerk et al, 1974). Using isogenic V. cholerae strains specifically mutagenized in the gene encoding NANase (nanH) and flow cytometry, Galen et al, (Galen et al, 1992) showed that fluorescence due to binding of fluoresceinconjugated CTX to mouse fibroblasts exposed to NANase-positive culture filtrates increased five-to eightfold relative to binding to cells exposed to NANase-negative filtrates.…”
mentioning
confidence: 96%
“…Choleragen also bound to liposomes containing GM1; this binding resulted in membrane damage (22,23), and membrane damage occurred only with the B protomer (24). Because choleragen could bind specifically to the oligosaccharide portion of GM1 (17,(25)(26)(27) and each toxin molecule could bind more than one molecule of this oligosaccharide (26, 27), we hypothesized that choleragen might exhibit lectinlike behavior at a membrane surface. In this paper we show that choleragen can agglutinate cells and liposomes containing GM1, as would be expected of a lectin or lectinlike protein.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the receptor for choleragen is ganglioside GM1 (11)(12)(13)(14)(15)(16)(17)(18). Binding of choleragen to lymphocytes resulted in patching and capping of membrane GM1 (19)(20)(21).…”
mentioning
confidence: 99%